2020
DOI: 10.1563/aaid-joi-d-19-00223
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Smoking on Dental Implant Osseointegration: A Radiofrequency Analysis of 194 Implants

Abstract: While many studies have related smoking to periimplantitis and marginal bone loss, little is known of its potential impact upon dental implant osseointegration. The present clinical study explores the influence of smoking upon secondary stabilization based on radiofrequency analysis. A total of 194 implants in 114 patients were included. Implant stability was evaluated on the day of surgery and a minimum of 90 days after implantation, when osseointegration is considered to have been completed. The evolution of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Implant losses may occur because of the absence of effective treatment approaches for PI. 16 In the videos evaluated, issues such as PI definition, etiology, risk factors, prevention, and treatment cost were mentioned less frequently, and treatment approaches were discussed a little more frequently. In fact, in the results of YouTube studies on dental implants, risk factors were not mentioned adequately enough, and the contraindications identified were not evidence based.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Implant losses may occur because of the absence of effective treatment approaches for PI. 16 In the videos evaluated, issues such as PI definition, etiology, risk factors, prevention, and treatment cost were mentioned less frequently, and treatment approaches were discussed a little more frequently. In fact, in the results of YouTube studies on dental implants, risk factors were not mentioned adequately enough, and the contraindications identified were not evidence based.…”
Section: Discussionmentioning
confidence: 99%
“…PI may have adverse effects on systemic health due to its inflammatory properties. Implant losses may occur because of the absence of effective treatment approaches for PI 16 . In the videos evaluated, issues such as PI definition, etiology, risk factors, prevention, and treatment cost were mentioned less frequently, and treatment approaches were discussed a little more frequently.…”
Section: Discussionmentioning
confidence: 99%
“…All patients in our study were non-smokers, as smoking is a significant risk factor for wound healing, augmentation procedures, and ultimately, the success rates of dental implants (Badenes & Pallarés, 2021). All the patients in the present study had healthy donor and recipient sites showing no residual infections to avoid disturbance in healing and bone formation (Tonetti et al, 1996).…”
Section: Discussionmentioning
confidence: 86%
“…The age group was selected between 20 and 60 years, as age is a crucial factor for bone maintenance, considering that bone mass density diminishes with aging (>60), which occurs in both male and female patients with age‐related osteoporosis (Manolagas, 2010). All patients in our study were non‐smokers, as smoking is a significant risk factor for wound healing, augmentation procedures, and ultimately, the success rates of dental implants (Badenes & Pallarés, 2021). All the patients in the present study had healthy donor and recipient sites showing no residual infections to avoid disturbance in healing and bone formation (Tonetti et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Most previous studies report that smoking tobacco does not have a significant impact on implant stability after full osseointegration [8][9][10][11][12]. A recent study revealed lower stability among smokers [13], while another indicated that primary stability may be higher in smokers versus nonsmokers [14]. Some researchers found that the process of osseointegration may be altered by tobacco use and that the process of acquiring secondary stability may be slower in smokers [11,12].…”
Section: Introductionmentioning
confidence: 99%